2017
DOI: 10.1016/j.ejphar.2016.11.050
|View full text |Cite
|
Sign up to set email alerts
|

D-Ala2-GIP-glu-PAL is neuroprotective in a chronic Parkinson's disease mouse model and increases BNDF expression while reducing neuroinflammation and lipid peroxidation

Abstract: Type 2 diabetes mellitus (T2DM) is a risk factor for Parkinson's disease (PD). Therefore, treatment to improve insulin resistance in T2DM may be useful for PD patients. Glucose dependent insulinotropic polypeptide (GIP) is a member of the incretin hormone family that can promote insulin release and improve insulin resistance. Several GIP analogues have been developed as potential treatments for T2DM. We had shown previously that D-Ala2-GIP-glu-PAL, a novel long-acting GIP analogue, can play a neuroprotective r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 59 publications
2
31
0
Order By: Relevance
“…Furthermore, another GLP-1 receptor agonist, exendin-4, has shown good protective effects in a pilot study in patients with Parkinson's disease [64]. It is therefore of interest to develop more efficient drugs that can activate not just GLP-1 but also the sister incretin signaling pathway GIP, which has shown neuroprotective effects on its own in preclinical studies of AD (Duffy and Holscher, 2013;Faivre and Holscher, 2013) and PD [65,66]. Novel dual agonists therefore may be superior in the clinic for treating chronic neurodegenerative disorders such as AD or PD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another GLP-1 receptor agonist, exendin-4, has shown good protective effects in a pilot study in patients with Parkinson's disease [64]. It is therefore of interest to develop more efficient drugs that can activate not just GLP-1 but also the sister incretin signaling pathway GIP, which has shown neuroprotective effects on its own in preclinical studies of AD (Duffy and Holscher, 2013;Faivre and Holscher, 2013) and PD [65,66]. Novel dual agonists therefore may be superior in the clinic for treating chronic neurodegenerative disorders such as AD or PD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MPTP treatment increased the levels of alpha-synuclein in the brain, and D-Ala2-GIP-glu-PAL reduced these levels to almost normal values. D-Ala2-GIP-glu-PAL also reduced the chronic inflammation response in the brain, reduced oxidative stress and lipid peroxidation, and increased the expression of Brain Derived Neurotrophic Factor (BDNF) (Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1 and GIP are members of the growth factor family (Holscher, 2014). We have previously shown that GLP-1 or GIP analogues enhance the expression of Brain-Derived Neurotrophic Factor (BDNF) (Ji et al, 2016b;Li et al, 2017), a growth factor that protects synaptic activity from stressors (Nagahara et al, 2009). GLP-1 and GIP can cross the BBB (Dogrukol-Ak et al, 2004;Hunter and Holscher, 2012;Kastin et al, 2002) and enhance the expression of key growth factors such as BDNF or GDNF.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose‐dependent insulinotropic polypeptide (GIP) is a sister hormone of GLP‐1 with similar properties as GLP‐1 (Lund, Vilsboll, Bagger, Holst, & Knop, ). GIP analogues have also shown neuroprotective effects in animal models of AD and Parkinson's disease (Duffy & Hoelscher, ; Faivre & Hoelscher, ; Li, Liu, Li, & Hoelscher, ; Li, Liu, Li, & Holscher, ).…”
Section: Introductionmentioning
confidence: 99%
“…GIP analogues have also shown neuroprotective effects in animal models of AD and Parkinson's disease (Duffy & Hoelscher, 2013;Faivre & Hoelscher, 2013;Li, Liu, Li, & Hoelscher, 2016;Li, Liu, Li, & Holscher, 2017).…”
Section: Introductionmentioning
confidence: 99%